PELUANG USAHA KRUPUK AMPLANG BERBAHAN DASAR IKAN BANDENG DI DESA ARGO MULYO KECAMATAN SEPAKU KABUPATEN PENAJAM PASER UTARA (PPU) - Misna Ariani; Didik Hadiyatno; Tutik Yulianni; Dwinda Tamara; Imam Ariwibowo (Jurnal Abdi Masyarakat Ilmu Ekonomi (JAMIE), 2023)
The training in this activity has the aim of increasing the knowledge of the women of Margo Mulyo Penajam Paser Utara (PPU) village by utilizing their businesses so that they can attract consumers to be loyal in making purchases so that it will increase income. For this reason, it is necessary to pay attention to a number of things, including: the ingredients and composition used, how to carry out the promotion, the product packaging that is owned and to display information that must be on the product packaging regarding the date of manufacture, expiration date, and product composition. Keywords: Amplang, Milkfish